Everyday multiculturalism : examining the daily interactions and lived experiences of local and migrant nurses - Melvin, Maahen (2017)
This study examines the daily interactions and lived experiences of both local and migrant nurses in the workplace setting. The influx of migrant nurses has made the nursing industry culturally diverse. While the state and healthcare employers assume that assimilation and integration would take place through current policies fostering multiculturalism. I argue that assimilation and integration is not an eventual outcome with the current state of multiculturalism. Despite numerous studies into the migrant nurses’ experience, there has been little research that has taken into account the perspectives of the local nurses. It seeks to fill the gap by examining both groups of nurses using the conceptual framework of multiculturalism and its current interpretation of “everyday multi-culturalism”. This study outlines how the interactions between local and migrant nurses are dynamic alternating between “conviviality” and “conflict” influenced and shaped by the “mixophilic” “mixophobic” policies of the state and health care industry.